2021
DOI: 10.3390/foods10071438
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Functional Food Processing

Abstract: Functional nutrition has become one of the main directions for a healthy lifestyle and sustainable food production due to its promising positive influence on health and its association with the use of raw materials of natural origin [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…China, Japan and Taiwan house the largest number of health food and beverage manufacturing global enterprises because their citizens are more concerned about health and believe that functional foods are a great way to take care of the body [ 59 , 60 ]. The main market trends that have been driving activity and growth in the functional food and beverage market are: Marketplace convergence of a range of categories; Accelerated growth in the number of functional foods and beverages; Cobranding partnerships between ingredient suppliers and manufacturers; Increased focus on science and validation of claims; Growing demand for sustainable and environmentally friendly food; Expansion of active nutrition products as consumers become more health-conscious; The emergence and popularity of innovative dosage and delivery forms; The rise of the millennials and a new paradigm on health and wellness [ 44 , 61 , 62 ]. …”
Section: Functional Beverages: Formulation and Classificationmentioning
confidence: 99%
“…China, Japan and Taiwan house the largest number of health food and beverage manufacturing global enterprises because their citizens are more concerned about health and believe that functional foods are a great way to take care of the body [ 59 , 60 ]. The main market trends that have been driving activity and growth in the functional food and beverage market are: Marketplace convergence of a range of categories; Accelerated growth in the number of functional foods and beverages; Cobranding partnerships between ingredient suppliers and manufacturers; Increased focus on science and validation of claims; Growing demand for sustainable and environmentally friendly food; Expansion of active nutrition products as consumers become more health-conscious; The emergence and popularity of innovative dosage and delivery forms; The rise of the millennials and a new paradigm on health and wellness [ 44 , 61 , 62 ]. …”
Section: Functional Beverages: Formulation and Classificationmentioning
confidence: 99%
“…Nowadays, consumers are increasingly seeking to find products that are safe and natural, have a generally recognized safe status, and are manufactured using innovative methods of sustainable and/or environmentally sound technologies (Vőneki et al, 2015). For this reason, the term "functional food" is becoming more common in the social and scientific fields, so the industry is continuously investing in the enhancement of manufacturing that can provide products with additional benefits for the consumer's health (Putnik & Kovačević, 2021). It was shown that health benefits and motivation for 71,3% 6,9% 21,9% I am pleased I expected more expensive using functional food are the strongest positive determinants of acceptance (Topolska et al, 2021).…”
Section: Factors Influencing Consumer Choices For Functional Foodsmentioning
confidence: 99%
“…They are an excellent way to supply nutrients and bioactive compounds, including vitamins, minerals, fiber, polyphenols, carotenoids, chlorophylls, tannins, etc. [ 2 , 5 ]. At present, indigenous fruits, which are economically poorly explored, represent an interesting niche for the development of novel functional juices [ 5 ], able to meet customer demand for natural beverages, with new sensory attributes and health-promoting properties [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 , 5 ]. At present, indigenous fruits, which are economically poorly explored, represent an interesting niche for the development of novel functional juices [ 5 ], able to meet customer demand for natural beverages, with new sensory attributes and health-promoting properties [ 6 ].…”
Section: Introductionmentioning
confidence: 99%